Malocclusion prevalence and comparison between the Angle classification and the Dental Aesthetic Index in scholars in the interior of São Paulo state - Brazil - Garbin, Artênio José Ísper [UNESP]; Perin, Paulo César Pereira [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Lolli, Luiz Fernando [UNESP] (FapUNIFESP (SciELO), 2010)
Introduction: The malocclusions are among the main buccal health problems all over the world, together with dental cavity and periodontal disease. Several indexes are being used for malocclusion registration. The present study verified the prevalence of this condition, using the Angle classification and the Dental Aesthetic Index (DAI), the severity and the necessity of orthodontic treatment registered with the DAI and the results of both indexes were compared, seeking to correlate collected data pattern and the viability of using them together. Methods: The sample consisted of 734 schoolchildren with 12 years of age, both male and female from the public municipal schools in Lins-SP, Brazil. The exams were performed at the school's playgrounds with the use of IPC probes with a naked eye. Results: For the Angle classification, it was found that 33.24% of the children presented normal occlusion and 66.76% presented malocclusions. It was observed, with the DAI, that 65.26% of the children had no abnormalities or had slight malocclusions. The defined malocclusion was present in 12.81%, severe malocclusion was observed in 10.90% and very severe or disabling malocclusion in 11.03%. Most of the children (70.57%) presented normal molar relationship and the anterior maxillary overjet was the most frequently observed alteration. When the indexes were compared there were similarities and divergences. Conclusion: DAI was not sensitive for some occlusion problems detected by the Angle classification, and vice-versa, demonstrating that both indexes have different points in malocclusions detection, so they could be used mutually in a complementary way.
Keywords: Angle classification; Dental Aesthetic Index; Index; Malocclusion; Prevalence